Epidemiology and teacher's perception of corporal punishment among students of Gampaha District. - Jayawardena, K.A.I.K (My University, 2003)
This study aimed at identifying the epidemiology and perception of teachers on corporal punishment among students aged 12-16yrs in Gampaha District. It was found that prevalence of corporal punishment is rather high in schools as well as at homes. The significantly associated factors are the male students and those who attend school from places other than home. The teachers although admit that corporal punishment has negative impact on students; they continue to use corporal punishment as disciplinary method. It is recommended to increase community awareness of negative impact of corporal punishment, of its ineffectiveness as disciplinary method aiming to change behavioral and attitudinal ideas of community. Teachers and parents should be made aware of alternative non-violent methods of disciplining the children.